Effect and process evaluation of a kindergarten-based, family-involved intervention with a randomized cluster design on sedentary behaviour in 4- to 6- year old European preschool children: The ToyBox-study. - Julie Latomme; Greet Cardon; Ilse De Bourdeaudhuij; Violeta Iotova; Berthold Koletzko; Piotr Socha; Luis Moreno; Odysseas Androutsos; Yannis Manios; Marieke De Craemer; ToyBox-study group (PLoS ONE, 2017)
BACKGROUND:The aim of the present study evaluated the effect and process of the ToyBox-intervention on proxy-reported sedentary behaviours in 4- to 6-year-old preschoolers from six European countries. METHODS:In total, 2434 preschoolers' parents/primary caregivers (mean age: 4.7±0.4 years, 52.2% boys) filled out a questionnaire, assessing preschoolers' sedentary behaviours (TV/DVD/video viewing, computer/video games use and quiet play) on weekdays and weekend days. Multilevel repeated measures analyses were conducted to measure the intervention effects. Additionally, process evaluation data were included to better understand the intervention effects. RESULTS:Positive intervention effects were found for computer/video games use. In the total sample, the intervention group showed a smaller increase in computer/video games use on weekdays (ß = -3.40, p = 0.06; intervention: +5.48 min/day, control: +8.89 min/day) and on weekend days (ß = -5.97, p = 0.05; intervention: +9.46 min/day, control: +15.43 min/day) from baseline to follow-up, compared to the control group. Country-specific analyses showed similar effects in Belgium and Bulgaria, while no significant intervention effects were found in the other countries. Process evaluation data showed relatively low teachers' and low parents' process evaluation scores for the sedentary behaviour component of the intervention (mean: 15.6/24, range: 2.5-23.5 and mean: 8.7/17, range: 0-17, respectively). Higher parents' process evaluation scores were related to a larger intervention effect, but higher teachers' process evaluation scores were not. CONCLUSIONS:The ToyBox-intervention had a small, positive effect on European preschoolers' computer/video games use on both weekdays and weekend days, but not on TV/DVD/video viewing or quiet play. The lack of larger effects can possibly be due to the fact that parents were only passively involved in the intervention and to the fact that the intervention was too demanding for the teachers. Future interventions targeting preschoolers' behaviours should involve parents more actively in both the development and the implementation of the intervention and, when involving schools, less demanding activities for teachers should be developed. TRIAL REGISTRATION:clinicaltrials.gov NCT02116296.